Hybridization of Step‐/Chain‐Growth and Radical/Cationic Polymerizations Using Thioacetals as Key Components for Triblock, Periodic and Random Multiblock Copolymers with Thermoresponsiveness. Issue 18 (4th May 2021) - Uchiyama, Mineto; Osumi, Masahiro; Satoh, Kotaro; Kamigaito, Masami
Abstract: A novel strategy for synthesizing a series of multiblock copolymers is developed by combining radical/cationic step‐growth polymerizations of dithiols and divinyl ethers and chain‐growth cationic degenerative chain‐transfer (DT) polymerizations of vinyl ethers using thioacetals as key components. The combination of radical step‐growth polymerization and a cationic thiol‐ene reaction or cationic step‐growth polymerization enables the synthesis of a series of macro chain‐transfer agents (CTAs) composed of poly(thioether) and thioacetal groups at different positions. The resulting products are 1) bifunctional macro CTAs with thioacetal groups at both chain ends, 2) periodic macro CTAs periodically having thioacetal groups in the main chain, and 3) random macro CTAs randomly having thioacetal groups in the main chain. Subsequently, the obtained macro CTAs are used for chain‐growth cationic DT polymerization of methoxyethyl vinyl ether (MOVE) to result in 1) triblock, 2) periodic, and 3) random multiblock copolymers consisting of poly(thioether) and poly(MOVE) segments. All these triblock and multiblock copolymers composed of hydrophobic poly(thioether) and hydrophilic poly(MOVE) segments show an amphiphilic tendency to form characteristic micelles in aqueous solutions. In addition, due to the thermoresponsive poly(MOVE) segments, the obtained copolymers exhibit lower critical solution temperatures that depend on the segment sequences and lengths. Abstract : A novel strategy for synthesizing a series of multiblock copolymers is developed by combining radical/cationic step‐growth polymerization of dithiols and divinyl ethers and chain‐growth cationic degenerative chain‐transfer polymerizations of vinyl ethers, using thioacetals as key components. The obtained triblock, periodic, and random multiblock copolymers consist of hydrophobic poly(thioether) and hydrophilic thermoresponsive poly(vinyl ether) and show characteristic aggregation and thermoresponsive behaviors. ​